2022
DOI: 10.2196/32832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of an App-Based Symptom Checker in Mental Disorders: Comparative Study in Psychotherapy Outpatients

Abstract: Background Digital technologies have become a common starting point for health-related information-seeking. Web- or app-based symptom checkers aim to provide rapid and accurate condition suggestions and triage advice but have not yet been investigated for mental disorders in routine health care settings. Objective This study aims to test the diagnostic performance of a widely available symptom checker in the context of formal diagnosis of mental disorde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 76 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…In addition, even when symptom checkers achieve high accuracy, their true value to the users can only be fully estimated when taking into account the users’ own appraisal, prior knowledge, and trust in the symptom checker [ 41 , 44 , 45 ]. Thus, an evaluation of symptom checkers with case vignettes alone is a useful but only a first step to identify the best symptom checkers; in a second step, the best-in-class apps should then be further evaluated with study designs where patients enter their own complaints [ 46 - 48 ], and patient-reported outcomes and experience measures should be brought into focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even when symptom checkers achieve high accuracy, their true value to the users can only be fully estimated when taking into account the users’ own appraisal, prior knowledge, and trust in the symptom checker [ 41 , 44 , 45 ]. Thus, an evaluation of symptom checkers with case vignettes alone is a useful but only a first step to identify the best symptom checkers; in a second step, the best-in-class apps should then be further evaluated with study designs where patients enter their own complaints [ 46 - 48 ], and patient-reported outcomes and experience measures should be brought into focus.…”
Section: Discussionmentioning
confidence: 99%
“…Although some apps are good at both triaging and diagnosis, no general association between an app’s triage and diagnostic ability exists to date. In addition, the accuracy of advice does not only vary considerably between symptom checkers but also within a given symptom checker, as it may prove more reliable in appraising some categories of diseases than others [ 48 ]. Taken together, these findings highlight that the current value of symptom checkers heavily depends not only on the app system but also on the question (use case) with which it is approached, for instance, whether to seek care or, if so, where or for what.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent clinical investigation in a mental health use case of Ada in an outpatient clinic, the average completion time of an Ada assessment was 7.90 (SD 3.39) minutes and an average of 31.90 (SD 8.11) questions were asked. 21 The Ada app is available both on Android and iOS devices in seven languages, and business-modified versions of the app can be found through various enterprise solutions with Ada business partners. A screenshot of the SAA used in the study in both English and Swahili is presented in figure 1 .…”
Section: Methods and Analysismentioning
confidence: 99%
“…In addition, even when symptom checkers achieve high accuracy, their true value to the users can only be fully estimated when taking into account the users' own appraisal, prior knowledge, and trust in the symptom checker [41,44,45]. Thus, an evaluation of symptom checkers with case vignettes alone is a useful but only a first step to identify the best symptom checkers; in a second step, the best-in-class apps should then be further evaluated with study designs where patients enter their own complaints [46][47][48], and patient-reported outcomes and experience measures should be brought into focus.…”
Section: Limitationsmentioning
confidence: 99%